IDENTIFICATION OF REGIONAL DEVELOPMENT PATTERN IN WEST JAVA USING THE MULTI-DIMENTIONAL SCALING AND FACTOR ANALYSIS METHOD - Wargyawati, Ni Made Gilang (Widyariset, 2013)
Application of the Multi-Dimensional Scaling (MDS) combined with Factor Analysis are able to extract dimensions or factors or components that affect the pattern of development in the area of West Java. Those dimensions are analyzed and inferred from selected regional growth variables which are translated from several relevant theories. The result of the Factor Analysis shows that there are two components that play a role in regional development in West Java. The first is the Human Resources (HR) which is derived from life expectancy, adult literacy, mean year of schooling, and road services variables. The another is concluded as economic factors which is derived from GDP per capita variabel and local investment. The two components or factors can explain about 69,60% of all variances. Combined with MDS, the analysis obtains 4 typologies of region, i.e. the region with both economic and HR factors are positive (+), the region with an economic factor (+), but the HR factor (-), the region with an economic factor (-), but a human factor (+), and the region with both economic and HR factors are negative (-). It can be concluded that the regional development in West Java requires a balanced concern over human and economic development. MDS results show economic growth is only enjoyed by few areas, so that the future needs of regional development should be based on typology obtained in this research.